Design and implementation of fingerprint access control system based on ZigBee wireless network - Zhang Jin; Jian Shaoyong (MATEC Web of Conferences, 2017)
this paper mainly introduces a kind of fingerprint access control system based on ZigBee wireless network design and implementation method, specify when passengers should fingerprints collected and stored in the system at the information desk PC, and then assign rooms;Guests entered the room according to the fingerprint module, the system will be fingerprint information through ZigBee coordinator node module and network to transmit the fingerprint characteristic value to management system and the fingerprint information stored, if consistent with the electromagnetic lock open, allowed to enter the room, does not conform to the issued a warning sound.Additional access control system can control the corresponding fingerprint information storage room and remove, such as is required for a security incident broke in situation is special open mode can be set up.System software design consists of two aspects of the bottom and upper machine.